First measurement of the Z→μ+μ- angular coefficients in the forward region of pp collisions at √s=13 TeV - Aaij, Roel; Abdelmotteleb, A. S. W.; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review letters, 2022)
The first study of the angular distribution of mu(+) mu(-) pairs produced in the forward rapidity region via the Drell-Yan reaction pp -> gamma*/Z + X -> l(+) l(-) + X is presented, using data collected with the LHCb detector at a center-of-mass energy of 13 TeV, corresponding to an integrated luminosity of 5.1 fb(-1). The coefficients of the five leading terms in the angular distribution are determined as a function of the dimuon transverse momentum and rapidity. The results are compared to various theoretical predictions of the Z-boson production mechanism and can also be used to probe transverse-momentum-dependent parton distributions within the proton.